Bullying behavior and mental health in healthcare and educational sectors in Kaunas, Lithuania - Lina Bernotaite; Vilija Malinauskiene; Palmira Leisyte (Nofer Institute of Occupational Medicine, 2017)
Background: Investigations on workplace bullying in the countries of Eastern Europe are yet not too extensive. The aim of the study has been to identify the most frequent bullying behavior and to explore the associations with psychological distress and post-traumatic stress symptoms in 3 female-dominated occupations in Kaunas, Lithuania. Material and Methods: This crosssectional study employed 517 teachers (response rate (RR) = 71.3%), 174 family physicians (RR = 65.7%) and 311 internal medicine department nurses (RR = 69.1%). The twenty-two-item Negative Acts Questionnaire was used for measuring the exposure to bullying behavior, Goldberg 12-item General Health Questionnaire (GHQ-12) - psychological distress, Event Scale-Revised (IES-R) inventory - post-traumatic stress symptoms, Karasek & Theorell Demand-Control questionnaire - psychosocial job characteristics. The International Business Machines Corporation (IBM) SPSS Statistics version 20.0 was used for performing the statistical analysis. Logistic regression was used for assessing the associations among 22 negative acts as continuous variable and mental health outcomes adjusting to age, psychosocial factors at work and everyday life. Results: Exposure to workplace bullying behavior on a weekly/daily basis was prevalent among family physicians at the rate of 19%, among nurses - 12.9%, among teachers - 4.1%. Even after adjustment to age, psychosocial job characteristics and threatening life events, the exposure to 22 negative acts as continuous variable was significantly associated with psychological distress and post-traumatic stress symptoms for all 3 occupations. Conclusions: Health care sector is particularly affected by workplace bullying. Exposure to bullying behavior was associated with mental health problems for all 3 occupations. Preventive measures are necessary to improve psychosocial work environment conditions in healthcare and educational institutions in Lithuania. Med Pr 2017;68(3):307-314